Musical Relationships: Towards a Phenomenological Analysis of Early Mother-Infant Interactions - David-Augustin MÂNDRUȚ (Studia Universitatis Babeș-Bolyai. Philosophia)
This paper investigates musical relationships in the case of the early mother-infant dyadic interactions. To accomplish this task, it is first needed to come back to some important authors from the tradition of both phenomenology and psychoanalysis. The theories of Husserl, Schutz and Taipale will prove themselves to be useful. Secondly, I shall deepen the investigation of the early mother-infant interactions through the prism of theories coming from Winnicott, Stern and Thomas Fuchs. My main task will be to demonstrate that these early interactions have a musical quality, similar to Colwyn Trevarthen’s thematization of communicative musicality. To prove my point, I have to first establish the features that make these early interactions be musical-like. Winnicott’s potential space and the example of babbling will follow my argumentation. I will also stress on the importance of the face-to-face interaction through affect attunement and mutual tuning-in. All these interactions are modes of being-with-another (Stern). An example will be found throughout this paper, namely a specific mode of being-with-another, which was called by Winnicott the primary maternal preoccupation.